2020
DOI: 10.3892/ol.2020.12206
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8‑negative effusion‑based lymphoma with indolent clinical behavior in an elderly patient: A case report and literature review

Abstract: Primary effusion lymphoma (PEL) is a B-cell non-Hodgkin's lymphoma that is usually characterized by lymphomatous effusions in the body cavity without any detectable tumor masses. According to the World Health Organization (WHO) schema for tumor classification, PEL is defined by the presence of human herpesvirus 8 (HHV8) in malignant lymphoid cells. However, a subset of effusion-based B-cell lymphoma is not HHV8-positive and exhibits different clinicopathological characteristics. The 2017 WHO Classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…PEL has been reported in HIV and HHV8-negative elderly patients without immunodeficiency [10,19,20,38]. In our previous study of 26 Taiwanese patients with a median age of 76.5, only one case was HIV-positive, while the others were either negative or presumed negative based on the clinical setting [10].…”
Section: Immunosenescencementioning
confidence: 92%
See 3 more Smart Citations
“…PEL has been reported in HIV and HHV8-negative elderly patients without immunodeficiency [10,19,20,38]. In our previous study of 26 Taiwanese patients with a median age of 76.5, only one case was HIV-positive, while the others were either negative or presumed negative based on the clinical setting [10].…”
Section: Immunosenescencementioning
confidence: 92%
“…In addition to the classic HHV8-related PEL, there are reports of sporadic cases and small series of HHV8-unrelated effusion lymphomas. Supplementary Table S1 lists all the HHV8-negative PEL cases in the English literature from 1996 to 2021 that we reviewed [4,7,[10][11][12][13][14]16,17,38,. There are a total of 167 cases, with the majority (92.2%, n = 154) being large cells with a B-cell phenotype, with rare cases of plasmablastic (3.0%; n = 5), T-cell (1.0%; n = 2), and indeterminate phenotype (3.6%; n = 6).…”
Section: Hhv8/kshv Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reports of PEBL have also interestingly documented complete remission following thoracentesis alone as well as spontaneous regression without any treatment whatsoever, with remissions lasting up to multiple years in certain cases. 7,9,19,21,27 This response of PEBL to drainage alone is in clear discrepancy with PEL as Alexanian et al's review notably reported that 70% of PEBL patients experienced partial or complete remission following thoracentesis alone as compared to only 18% of PEL patients. 5 Although thoracentesis alone is a promising treatment option, we propose that thoracentesis alongside R-CHOP should be used in eligible patients since the data supporting thoracentesis alone is quite limited at this time.…”
Section: Discussionmentioning
confidence: 99%